Impact of DG on Voltage Profile and Power Losses for 33/11kV PPU Bakar Batu and PPU Century (Johor Bharu) using PSCAD Software - Mohd Hendra Hairi; W.X. Juan; M.N. Kamarudin; A.S M. Isira; M.F.P. Mohamed; S. A. Sobri (International Journal of Electrical Engineering and Applied Sciences, 2022)
Distributed Generation (DG) has become the world's primary focus for solving the energy crisis and pollution. Therefore, it is crucial to investigate the impacts of DG on the existing radial distribution network to ensure the reliability and efficiency of the network. This paper presents the impact of DG in terms of voltage profile and power losses in the Malaysia distribution network. A 33/11kV Medium Voltage (MV) distribution network based in PPU Bakar Batu and PPU Century, Johor Bharu has been modelled and simulated by using PSCAD/EMTDC simulation software. Several cases with different location of DG placement and size of DG has been carried out in this study. The simulation results show an improvement of voltage profile within the allowable limit of 0.95p.u and 1.05p.u and a minimization of power losses after DG is installed in the network. The suggestions to the optimal location for DG installation is analyzed based on the results of the pre and post interconnection of DG